Management of Improving the Quality of Social Science Learning Based on Information and Communication Technology in South Jakarta Junior High Schools - Suhaimi, Ahmad; Wasliman, Iim; Sauri, R. Supyan; Kosasih, Usep (International Journal of Science Education and Technology Management, 2023)
Social Science Learning is a simplified social science for educational purposes covering aspects of historical science, economic science, political science, sociology, anthropology, psychology, geography and philosophy. And the definition of information and communication technology is a technology used to process data, including processing, obtaining, compiling, storing, manipulating data in various ways to produce quality information, namely relevant, accurate and timely information, which is used for personal, business , and government purposes is also strategic information for decision making Improving the quality management of Social Science learning based on media Information and communication technology aims to improve the quality of Social Science learning education in high school education, especially in the south of Jakarta. Information and communication technology also has several objectives and benefits, this research method, namely qualitative, is descriptive analysis. The descriptive method of analysis is a method or way of working in a problem solving by describing, describing, explaining and analyzing the research carried out. Of course, in this case, it is how the school provides educators with an understanding of social science learning based on information and communication technology to improve the quality of education.